Device Free Localization with Capacitive Sensing Floor - Faulkner, Nathaniel; Parr, Baden; Alam, Fakhrul; Legg, Mathew; Demidenko, Serge (2020 IEEE Sensors Applications Symposium (SAS), 2020)
Passive indoor positioning has many applications including intrusion detection, fall detection of the elderly, and occupancy sensing to name a few. However, current Device Free Localization (DFL) solutions fall short of the desired accuracy requirements and are difficult to implement in a real-world scenario. This research investigates the use of a capacitive floor-based sensing solution, which can simultaneously detect multiple footsteps of a subject. The developed sensing floor prototype achieved a median positioning error of 13.5 mm and a median angular accuracy of 10.4°.